The effects of imagery interventions in sports: a meta-analysis. Issue 1 (1st January 2021) - Simonsmeier, Bianca A.; Andronie, Melina; Buecker, Susanne; Frank, Cornelia
ABSTRACT: Imagery interventions are an established psychological tool to enhance performance, psychological skills, and injury rehabilitation. Previous meta-analyses found positive effects of mental practice on performance, leaving it open whether imagery can also enhance outcomes other than performance such as motivational or affective outcomes. We performed a meta-analysis to extend the current understanding of the effectiveness of imagery in sports on any sport specific outcome and the relevance of additional variables potentially moderating the effect. The overall effect of imagery interventions was medium in magnitude with d  = 0.431 (95% CI [0.298, 0.563]). Imagery interventions significantly enhanced motor performance, motivational outcomes, and affective outcomes. Summarized across all outcomes, imagery combined with physical practice was more effective than physical practice alone, indicating differential effects of imagery and physical practice. We found the same pattern of result for performance outcomes. The effectiveness of imagery was positively associated with the intensity of the imagery training. We discuss our results against previous meta-analyses on mental practice and the background of theoretical and practical aspects of imagery. Moreover, we lay out directions for future research by providing a comprehensive overview of research gaps in the literature on imagery.